Design of a photovoltaic MPPT charge controller using DC-DC ZETA converter with a modified three-stage charging method - Sina Semeskandeh; Mehrdad Hojjat; Mohamad Hosseini Abardeh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Nowadays, one of the primary kinds of renewable energies is photovoltaic (PV) systems. In standalone PV systems, the battery charge controller plays an important role in the system efficiency. In the maximum power point tracking (MPPT) charge controller, due to adjusting the voltage level and tracking the maximum power, DC-DC converter and MPPT algorithm are used. ZETA converter, as a DC-DC converter, offers a low output ripple. In the proposed MPPT charge controller, a DC-DC ZETA converter accompanied by a perturb and observe (P&O) algorithm will be used for tracking maximum power. Furthermore, over-charging and gassing are phenomena that may reduce the battery life by increasing the battery's temperature. To overcome this obstacle, the proposed three-stage charging method, which is the battery charging voltage levels (bulk, absorption, and float) are based on the battery temperature. The proposed MPPT charge controller is used for providing lower temperature for the battery when being charged. By comparing the proposed MPPT charge controller with the conventional method, the simulation results can ensure the desired performance of the proposed charge controller.